2012
DOI: 10.4028/www.scientific.net/amm.229-231.1437
|View full text |Cite
|
Sign up to set email alerts
|

Carbaryl Detection by Gold Nanoparticles Electrodes for Fruit Application Model

Abstract: A new method has been developed for the determination of carbaryl pesticides, , in water and fruit samples using gold nanoparticles electrode conductivity detection. The effects of pH on the binding between carbaryl and humic acid (HA) and number of layer coated electrode were investigated and optimized. HA modified the polyelectrolyte multilayer thin films (PEMs) coating electrode was used to detect carbaryl. The current was decreased 4.75% after dipping in HA for 10 minutes. The current was decreased around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Additives to the monomer solution as commonly proposed in the literature , , were also tested. Benzyl alcohol is typically added as a chain transfer agent, limiting polymer brush size and suppressing polymerization around nucleation seeds within the solution. , However, high concentrations of chain transfer agent significantly reduce the grafting density (Figure d). Addition of NaIO 4 is frequently proposed in the literature in order to act as an oxygen scavenger. ,, In our tests, we found that with properly degassed monomer solutions and with BP acting as an oxygen scavenger in the PDMS matrix beneficial effects from NaIO 4 are very limited.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additives to the monomer solution as commonly proposed in the literature , , were also tested. Benzyl alcohol is typically added as a chain transfer agent, limiting polymer brush size and suppressing polymerization around nucleation seeds within the solution. , However, high concentrations of chain transfer agent significantly reduce the grafting density (Figure d). Addition of NaIO 4 is frequently proposed in the literature in order to act as an oxygen scavenger. ,, In our tests, we found that with properly degassed monomer solutions and with BP acting as an oxygen scavenger in the PDMS matrix beneficial effects from NaIO 4 are very limited.…”
Section: Resultsmentioning
confidence: 99%
“…Benzyl alcohol is typically added as a chain transfer agent, limiting polymer brush size and suppressing polymerization around nucleation seeds within the solution. 13,50 However, high concentrations of chain transfer agent significantly reduce the grafting density 6 (Figure 2d). Addition of NaIO 4 is frequently proposed in the literature in order to act as an oxygen scavenger.…”
Section: Table 1 Significant Parameters For the Polymerization Treatm...mentioning
confidence: 98%